If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m = 3n + -4 Reorder the terms: m = -4 + 3n Solving m = -4 + 3n Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Simplifying m = -4 + 3n
| l(m)=3n-4 | | 2z(4z+12)=8z^2+24z-5 | | v=1/3(3.14) | | h(m)=-2(n+2)-6 | | 0.15p=2.4 | | 0.7x+0.7=6.3 | | log(x+5)-logx=3 | | 5+6=2x | | 2.7=6.5+y | | 2h^2+7h+3=20 | | x=-49/93 | | m=2(n+2)-6 | | 2.9=6.9+y | | x^2+6x-21=x | | 10x^2-27x+18.22=0 | | (x)(x+6)=432 | | 7(n-3)=-35 | | 8p+2=5p-4 | | 31=7-4h | | Q(Q)=0 | | 5x=15+2y | | Q(q-5)=0 | | 3x+1=5x+49 | | 5x+49=3x+1 | | X^2-34x+281=0 | | 480-x/16 | | 2y^2-17y+45=(y-7)(y-7) | | -8n-4+2n= | | 2x^2-18x=-9x | | (x+4)(x-1)=-6 | | b=3a-aw | | 5x=2x+28 |